2-adic complexity of SLCE sequence - Yan WANG; Shunbo LI; Gaina XUE (Tongxin xuebao)
Aiming at the 2-adic complexity of Sidelnikov-Lempel-Cohn-Eastman sequences,autocorrelation function value of this kind of sequence was obtained by using the cyclotomic number.Based on the relationship between 2-adic complexity and autocorrelation function,properties of 2-adic complexity value were analyzed.According to the greatest common divisor between the autocorrelation function value and the period of SLCE sequence,the condition that the 2-adic complexity of a SLCE sequence reaches its maximum value was given.The results show that 2-adic complexity of SLCE sequence on many finite field can reach the maximum value.